Analysis of cycle observation sheets in a group of women of reproductive age - Piasecka, Katarzyna; Łyszczarz, Paulina; Pytka, Monika; Ślizień-Kuczapska, Ewa; Kanadys, Katarzyna (Kwartalnik Naukowy Fides et Ratio, 2022)
Background: Knowledge concerning value of menstrual cycle observation and its use to monitor procreative health is underestimated and limited in women’s health promotion, education and health care. Academy of Pediatrics, Committee on Adolescence and , American College of Obstetricians and Gynecologists recommends starting to observe the forming cycle as early as puberty in order to pre-screen girls , from groups at risk of fertility disorders such as polycystic ovary syndrome. In view of the numerous reports on the increase in fertility problems, such a simple tool as self-observation of the menstrual cycle becomes particularly useful to learn about the natural rhythm of fertility and in the case of abnormalities, i.e. deviation from the typical course shortens the time to the first medical consultation. In Poland there are several non-governmental non-profit organizations, which through certified teachers of fertility awareness methods can professionally support the teaching of adolescents, adults and interested people working in the health service in the field of fertility awareness, health education and natural family planning. Aim of the presented study was to analyze 105 menstrual cycle observation charts among polish women not using contraception according to the principles of the symptom-thermal double-check method. Method: The study was performed using the method of documentation analysis, 105 menstrual cycle observation charts using the statistical package SPSS Statistica version 25. The level of p < 0.05 was considered statistically significant. Results: The average age of the women studied was 29 years. The majority of the women , i.e. more than 58%, were unmarried and childless (79.1%). The average length of the menstrual cycle was: 28.6 days. The average duration of the luteal phase was almost 13 days. The average length of days of highly fertile mucus was nearly 4 days. The average length of cycles of women over 35 years of age was: 28.88 days, while for women under 35 years of age. 28.48 days. The age of onset of the first menstrual period of the women studied varied between 10 and 17 years of age. Conclusions: The studied group of women was homogeneous in terms of the adopted eligibility criteria, i.e. they had typical cycles and did not use contraceptive methods. The examined parameters of the menstrual cycle, i.e.: the average length of the cycle , the course of the luteal phase and the average length of the occurrence of highly fertile mucus met the criteria for a normal cycle according to the symptom-thermal double-check method.